N-acetylserotonin activates TrkB receptor in a circadian rhythm - Jang, Sung-Wuk (National Academy of Sciences, 2010)
Brain-derived neurotrophic factor (BDNF) is a cognate ligand for the TrkB receptor. BDNF and serotonin often function in a cooperative manner to regulate neuronal plasticity, neurogenesis, and neuronal survival. Here we show that NAS (N-acetylserotonin) swiftly activates TrkB in a circadian manner and exhibits antidepressant effect in a TrkB-dependent manner. NAS, a precursor of melatonin, is acetylated from serotonin by AANAT (arylalkylamine N-acetyltransferase). NAS rapidly activates TrkB, but not TrkA or TrkC, in a neurotrophin- and MT3 receptor-independent manner. Administration of NAS activates TrkB in BDNF knockout mice. Furthermore, NAS, but not melatonin, displays a robust antidepressant-like behavioral effect in a TrkB-dependent way. Endogenous TrkB is activated in wild-type C3H/f(+/+) mice but not in AANAT-mutated C57BL/6J mice, in a circadian rhythm; TrkB activation is high at night in the dark and low during the day. Hence, our findings support that NAS is more than a melatonin precursor, and that it can potently activate TrkB receptor.